Pengaruh Pengungkapan Kınerja Keuangan Pemerıntah, Temuan Pemeriksaan Badan Pemeriksa Keuangan terhadap Opini Audit dengan Tindak Lanjut Hasil Pemeriksaan sebagai Variabel Pemoderasi - Syaputra, Tirtha; Hasan, Amir; Rasuli, Rasuli (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This research aims to analyze the effect of Financial Performance, SPI Examination Findings, and Compliance with Legal Provisions on Audit Opinion. As well as to find out whether The Following Examination Results moderates the relationship of Financial Performance, Audit Findings on SPI, and Compliance with Legal Provisions on Audit Opinions. This research is a quantitative study using secondary data sourced from the BPK Examination Report (LHP) on Provincial, District/ City LKPD in Riau for years 2014-2017. The number of samples in this study were 52 LKPD from 13 LGs for 4 years. Data processing uses statistical methods of PLS- SEM with the help of WarpPLS 5.0 Software. In analyzing data to be performed is the Measurement Model test (outer model), and Evaluation of Structural Model (inner model). The results of the research revealed that the Internal Control System had significant negative effect on Audit Opinion, and the Following Examinations Results moderated the relationship of Non-compliance with Legal Provisions to Audit Opinion. Financial Performance and Non-compliance with Legal Provisions was not affect Audit Opinion, as well as the Following Examinations Results was not moderating the relationshiip between Financial Performance and Internal Control System to Audit Opinion.